Investigations on apoptosis-associated caspase activation cascades - Murphy, Brona (Trinity College (Dublin, Ireland). Department of Genetics, 2004)
Apoptosis is an important process in a wide variety of different biological systems such as the immune system, normal cell turnover and embryonic development (Stennicke et al., 2002). Apoptosis is characterized by a series of distinct morphological and biochemical alterations such as DNA fragmentation, chromatin condensation, cell shrinkage and membrane blebbing (Adrain and Martin, 2001). In mammalian systems, the core component of the death machinery responsible for these stereotypic changes is a family of proteases known as caspases (Earnshaw et al., 1999). The mammalian caspases may be divided into two broad subfamilies, the caspase-1 subfamily and the CED-3 subfamily. The CED-3 subfamily includes caspases -2, -3, -6, -7, -8, -9 and -10. These caspases are directly involved in apoptosis (Earnshaw et al., 1999; Lamkanfi et al., 2002). The research outlined in this thesis addresses these apoptotic caspases and in particular, the mechanisms governing the activation and regulation of these key proteases.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin